(untitled) (Research, Society and Development, 2022)
This study aimed to analyze the pharmacotherapeutic and laboratory profile of patients with secondary hyperparathyroidism submitted to Parathyroidectomy and followed up at the nephrology outpatient clinic of a University Hospital. This is a descriptive, cross-sectional, retrospective and quantitative study, collecting data from January 2003 to January 2020, carried out at the Nephrology outpatient clinic of the Hospital das Clínicas of the Federal University of Pernambuco (HC/UFPE), in the city of Recife - PE. The collected data were tabulated in an electronic spreadsheet. For the descriptive analysis of the collected data, measures of frequency, mean, standard deviation and mode were used. The study included 91 patients, whose mean age was 48.1 years (± 12.4) and the majority was greater than or equal to 59 years (82.4%), female (68,1%), self-declared black/ brown (90.1%), single (49.5%), with incomplete primary education (24.2%) and residing in rural areas (87.9%). The diagnosis of undetermined etiology had the highest prevalence (41.8%). Most had disease prior to CKD (56.0%) and were not submitted to conservative treatment (76.9%). Laboratory parameters varied over the follow-up period. The main drugs used by patients were calcium carbonate 500mg (100%); calcitriol 0.25mcg (96.7%); sevelamer 800mg (85.7%); and cinacalcete 30mg (21.9%). The multifaceted approach remains at the forefront of treatment, with no single intervention measure being considered superior. Parathyroidectomy remains a valid treatment option for patients who are refractory to drug therapy and should continue to be considered whenever there is a medical indication.